2011
DOI: 10.1108/07378831111116976
|View full text |Cite
|
Sign up to set email alerts
|

Online databases and the research experience for university students with print disabilities

Abstract: PurposeThe purpose of this paper is to present findings of a study which examined the searching experience of university students with a print disability and their use of screen reading software to navigate three proprietary databases.Design/methodology/approachParticipants completed a series of tasks in three different online databases using their screen‐reading software. Screen‐recording software provided video and audio documentation of the process. Survey data were collected pre‐ and post‐study as well as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
0
32
0
3
Order By: Relevance
“…Their self-efficacy as independent learners is challenged every time they encounter an unreadable PDF or take up to eight hours to find four articles. 48 Universal design is a concept that originated in architecture and the built environment. Perhaps its most cited example and metaphor is the curb cut, mandated and designed for wheelchairs but appreciated by anyone with a stroller, shopping cart, bicycle, or rolling suitcase.…”
Section: December 2012 Research Library Issues: a Quarterly Report Frmentioning
confidence: 99%
“…Their self-efficacy as independent learners is challenged every time they encounter an unreadable PDF or take up to eight hours to find four articles. 48 Universal design is a concept that originated in architecture and the built environment. Perhaps its most cited example and metaphor is the curb cut, mandated and designed for wheelchairs but appreciated by anyone with a stroller, shopping cart, bicycle, or rolling suitcase.…”
Section: December 2012 Research Library Issues: a Quarterly Report Frmentioning
confidence: 99%
“…10 Dermody and Majekodunmi found that students were hindered by advanced database features intended to improve general users' experiences. 11 Disabled students were also confronted with excessive links, unreadable links, and inaccessible PDFs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 Similarly, Dermody and Majekodunmi found that students with print-related disabilities who use screen-reading software could only complete 55 percent of tasks successfully because of accessibility barriers and usability challenges. 12 DeLancey surveyed vendors and examined VPATs, or product accessibility claims, and found that vendors felt they were compliant with 64 percent of US Section 508 items. 13 Especially relevant to this study, only 23 percent of vendors said that the multimedia content within their products was compliant, and 46 percent admitted multimedia content was not compliant at all.…”
Section: Literature Reviewmentioning
confidence: 99%